Efeito da restrição alimentar inicial e da temperatura ambiente sobre o desenvolvimento de vísceras e ganho compensatório em frangos de corte - Furlan, R. L. [UNESP]; Carvalho, N. C. [UNESP]; Malheiros, E. B. [UNESP]; Macari, Marcos [UNESP] (FapUNIFESP (SciELO), 2001)
The aim of this investigation was to evaluate the effect of feed restriction and environmental temperature on viscera development and compensatory gain of broiler chickens. Five hundred and forty male chickens were used, in a completely randomized design in a factorial arrangement 2×3 (two feeding programs - ad libitum and feed restriction from 7 to 14 days) and three environmental temperatures - hot, thermoneutral and cold), Feed restriction did not affect the liver and heart relative weight, but significantly decreased intestine weight and length by the end of restriction period (14 days of age). No significant differences were observed between feeding program for viscera relative weight at 42 days of age. Broiler early restrictedly fed showed lower body weight, body weight gain and feed consumption at 28 days, but no differences were found among these variables at 42 days, as a consequence of the compensatory gain during the refeeding period. The viscera relative weights were not affected by environmental temperature at 42 days, except the heart. Birds growing in high environmental temperatures had lower feed consumption, body weight and body weight gain at 42 days of age.
Effect of early quantitative feed restriction and environmental temperature on viscera growth and compensatory gain of broiler chickens
Keywords: Broiler chicken; Compensatory gain; Feed restriction; Temperature; Viscera